[OP.8E.08] REGIONAL VARIATIONS IN THE ASSOCIATIONS OF DIETARY PATTERNS WITH BLOOD PRESSURE AND HYPERTENSION IN SWITZERLAND. (September 2016) - Burnier, M.; Chappuis, A.; Glatz, N.; Bochud, M.
Abstract : Objective: Nutritional factors play an important role in the regulation of blood pressure (BP) and in the development of hypertension. The quality of food is influenced by regional habits. We explored the associations of serum Na+, K+, Ca++ and urea and their urinary excretions with BP level and the risk of hypertension in the Swiss population taking regional linguistic differences into account. Design and method: The Swiss Survey on Salt is a population based, cross sectional study that included 1336 subjects from the 3 main linguistic (French, German and Italian) regions of Switzerland. BP was measured with a validated device. Hypertension was defined as current antihypertensive treatment or a mean systolic BP >140 mmHg and/or diastolic > 90 mmHg, based on 8 BP measures. Na, K, Ca++ and urea excretions were assessed in 24-hour urine collections. Multiple logistic/linear regression explored the associations with BP/hypertension. Results: In the Swiss population, besides age, sex, and body mass index, urinary sodium excretion was positively associated with systolic and diastolic BP and hypertension. The slope of the association was comparable in men and women but steeper in subjects >50 y of age and overweight subjects (Figure). Urinary K excretion was not associated with BP unless urinary Na excretion was included in the model. Urinary calcium and urea excretion were not associated with BP. When compared to normotensive, hypertensive participants were characterized by a higher urinary Na but lower urinary K excretion and protein intake. Participants of the German-speaking regions had a higher likelihood of having a high BP and being hypertensive. The prevalence of hypertension was higher in German-speaking participants: this was true for men but not for women. Figure. No caption available. Conclusions: In Switzerland, urinary Na excretion is associated positively with BP and hypertension with a greater effect in subjects > 50 y and overweight subjects. Potassium modulates the effect of sodium on BP. A higher prevalence of hypertension is found in the German-speaking region of Switzerland due, in part, to dietary factors. These results highlight the importance of nutritional factors in hypertension and emphasize the need to adapt national prevention strategies to regional considerations.